Understanding climate-induced migration in West Africa through the social transformation lens - Osei-Amponsah, Charity; Quarmine, William; Okem, Andrew (Frontiers Media, 2023)
The climate crisis has migration implications, and we need to act inclusively and urgently. Climate change impacts people’s decisions to migrate largely through economic, political, technological, demographic, and sociocultural factors, and their dynamic interlinkages. These complex issues often influence climate risks and vulnerabilities and complicate effective investment and policy actions on migration. However, there is inadequate documentation on how climate change is linked to migration and social transformation. Based on a traditional literature review and inputs from a consultation dialogue, this paper analyzes climate-induced migration in West Africa using a social transformation lens. The paper conceptualizes the climate-induced migrant as an agent of adaptation and describes the complexities of climate vulnerabilities, and its intersection with social transformation in migration decisions. A social transformation conceptual framework is proposed to identify the complexities of climate-induced migration and ensure inclusive strategies are planned, implemented, and sustained. The paper discusses the need for transdisciplinary research approaches to capture various intersections of transforming socioeconomic and environmental vulnerabilities across different countries and migratory landscapes. The paper also highlights the critical concern in the region regarding the “trapped population.” It suggests that a social transformation lens is required to unravel the dynamics around vulnerable people unable to migrate because they do not have the resources to migrate or are constrained by cultural issues.